# step by step and prove it

Attachments:

AbhishGS:
wait ...I can try to find .

## Answers

Answered by

1

Hope it helps. thnx and click on brainliest

Attachments:

Answered by

0

cosec A + cot A - 1 / cot A - cosec A + 1

we know that,cosec ² A - cot ² A = 1

substituting this in the numerator

cosec A + cot A -(cosec ² A - cot ² A) / (cot A - cosec A + 1)

x²-y²= (x+y)(x-y)

cosec A + cot A - (cosec A + cot A) (cosec A - cot A) / (cot A - cosec A + 1)

taking common

(cosec A + cot A)(1-cosec A + cot A) / (cot A - cosec A + 1)

cancelling like terms in numerator and denominator

we are left with cosec A + cot A

= 1/sin A + cos A/sin A

= (1+cos A) / sin A

we know that,cosec ² A - cot ² A = 1

substituting this in the numerator

cosec A + cot A -(cosec ² A - cot ² A) / (cot A - cosec A + 1)

x²-y²= (x+y)(x-y)

cosec A + cot A - (cosec A + cot A) (cosec A - cot A) / (cot A - cosec A + 1)

taking common

(cosec A + cot A)(1-cosec A + cot A) / (cot A - cosec A + 1)

cancelling like terms in numerator and denominator

we are left with cosec A + cot A

= 1/sin A + cos A/sin A

= (1+cos A) / sin A

Similar questions